15 Minutes Reading Program in Ma’arif Islamic Senior High School - Luthvi Al Hasyimi, Muhammad (STAI MA'ARIF MAGETAN, INDONESIA, 2022)
This study is aimed to find out the school literacy program which has actually been promoted by the government since 2015 in Ma’arif Islamic Senior High School, Karangrejo. The fact that the program has been running the program for 2 years brings question whether the program is in line with the government or not. Moreover, social practice in the schools is also interesting to be explored. Purposefully, it is considered to develop students’ and teachers’ literacy practice in terms of reading various kinds and genres of books. In particular, 32 first grade students, 29 second grade students, and 30 third grade students of the Senior High School, also 5 “local-course” teachers, 2 Indonesian language teachers, 2 Arabic teachers, and 1 English teacher have been interviewed. Additionally, the 15 minutes reading program in every class has been observed. The information collected represents the data to be analyzed. This research is conducted using descriptive qualitative method to determine the data. Based on the findings and the discussion, this research figured out that the literacy program in this school is not centered to the government’s guidance.